First trimester sCD40L levels associated with adverse neonatal outcomes in euthyroid pregnant women with positive TPOAb - Chen, Xinxin; Wang, Qingyao; Zang, Huanhuan; Cong, Xiangguo; Shen, Qiong; Chen, Lei (Frontiers in Endocrinology, 2023)
ABSTRACT Backgrounds: It remained unclear whether isolated positive TPOAb was associated with adverse maternal and neonatal outcomes. The purpose of this study was to observe adverse neonatal outcomes among euthyroid pregnant women with positive TPOAb and to investigate the underlying risk factors. Methods: Euthyroid pregnant women with TPOAb positivity were enrolled and followed up in our study. Adverse neonatal outcomes such as preterm birth, low birth weight, fetal macrosomia, were observed. Clinical data in the first trimester were collected and compared between groups with or without adverse neonatal outcomes. Maternal serum soluble CD40 ligand (sCD40L) was also measured at the same time. Results: A total of 176 euthyroid pregnant women with TPOAb positivity were finally enrolled and analyzed in our study. 39 (22.16%) euthyroid women with TPOAb positivity were found to have adverse neonatal outcomes. There were 13 participants received assisted reproductive technology (ART) in our study and 7 were in adverse neonatal outcome group. Preterm birth, low birth weight and fetal macrosomia were the most common comorbidities. The proportion of receiving ART, sCD40L and platelet were significantly higher in the adverse neonatal outcome group (all P <0.05). Multivariate regression analysis showed that sCD40L and receiving ART were independent risk factors for adverse neonatal outcomes. The odds ratio (OR) value of sCD40L higher than 5.625ng/ml were 2.386 (95% confidence incidence (CI) =1.017 to 5.595; P = 0.046) for overall adverse neonatal outcome, 3.900 (95% CI =1.194 to 12.738; P = 0.024) for preterm birth, and 3.149 (95% CI =0.982 to 10.101; P = 0.054) for low birth weight respectively. Conclusions: Approximately 1/4 of euthyroid women with TPOAb positivity might have adverse neonatal outcomes. Measurement of sCD40L in first trimester might have predictive value for adverse neonatal outcomes in euthyroid pregnant women with positive TPOAb.